Correlation between Metacognitive Awareness and Students’ Self-Efficacy in Chemistry Learning among Grade XII Students - Mutiara Tsani; Erlina; Eni Mayasari (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to identify the relationship between metacognitive awareness and students’ self-efficacy in chemistry learning among grade XII students at MAN Pontianak. This research employed a quantitative approach with a descriptive correlational design involving 36 students selected through purposive sampling. The instruments used were the Metacognitive Awareness Inventory (MAI) questionnaire and a self-efficacy questionnaire, both of which had been validated and tested for reliability. Data were analyzed using descriptive statistics and the Pearson Product-Moment correlation test. The results showed that students’ metacognitive awareness was predominantly in the very well-developed category (66.7%), while self-efficacy was classified as very high (91.7%). The correlation analysis revealed a positive but weak and statistically insignificant relationship between metacognitive awareness and self-efficacy (r = 0.249; p = 0.144 > 0.05). These findings indicate that although both variables are at high levels, metacognitive awareness does not necessarily predict students’ self-efficacy in chemistry learning. This study contributes to the understanding of the complex interaction between cognitive and affective factors in chemistry education. Practically, the results suggest that teachers should not only develop students’ metacognitive skills but also implement instructional strategies that explicitly strengthen self-efficacy, such as providing mastery experiences, constructive feedback, and problem-based learning environments.